دافعية التعلّم وعلاقتها بالتحصيل الدراسي لدى تلاميذ المرحلةالثانوية – دراسة ميدانية بثانويةزيري بن مناد ببوسعادة- - سقاي ليلى.; بوعداوي مباركة; طيباوي السعدية (جامعة محمد بوضياف -المسيلة, 2025)
هدفت هذه الدراسة إلى البحث عن العلاقة بين دافعية التعلّم والتحصيل الدراسي لدى تلاميذ ثانوية زيري بن مناد ببوسعادة، كما هدفت للبحث عن مستويي الدافعية والتحصيل الدراسي لدى العيّنة، كما بحثت في الفروق في الدافعية لدى العيّنة تبعا لمتغيري الجنس والسنّ، حيث كان حجم عينة الدراسة من تلاميذ السنة الثانية ثانوي 210 فردا، وطبقت المنهجالوصفي الارتباطي بأسلوب المقارنة، وتوصّلت إلى النتائج التالية: - توجد علاقة ارتباطية قويّة ذات دلالة إحصائية بين دافعية التعلّم و التحصيل الدراسي لدى تلاميذ ثانوية زيري بن مناد ببوسعادة. توجد علاقة ارتباطية قوية ذات دلالة إحصائية بين المشاركة و التحصيل الدراسي لدى تلاميذ ثانوية زيري بن مناد ببوسعادة. - توجد علاقة ارتباطية قوية ذات دلالة إحصائية بين الفعالية و التحصيل الدراسي لدى تلاميذ ثانوية زيري بن مناد ببوسعادة. - توجد علاقة ارتباطية قوية ذات دلالة إحصائية بين الاهتمام و التحصيل الدراسي لدى تلاميذ ثانوية زيري بن مناد ببوسعادة. - توجد علاقة ارتباطية قوية ذات دلالة إحصائية بين تحمّل المسؤولية و التحصيل الدراسي لدى تلاميذ ثانوية زيري بن مناد ببوسعادة. - مستوى دافعية التعلّم لدى تلاميذ ثانوية زيري بن مناد ببوسعادة مرتفع. - مستوى التحصيل الدراسي لدى تلاميذ ثانوية زيري بن مناد ببوسعادة مرتفع. -لا توجد فروق ذات دلالة إحصائية في دافعية التعلّم لدى تلاميذ ثانوية زيري بن مناد ببوسعادة تعزي لمتغير الجنس. -لا توجد فروق ذات دلالة إحصائية في دافعية التعلّم لدى تلاميذ ثانوية زيري بن مناد ببوسعادة تعزي لمتغير السنّ. الكلمات المفتاحية: -دافعية التعلّم –التحصيل الدراسي–تلاميذ التعليم الثانوي. ملخص الدراسة باللغة الانجليزية Abstract : This study aimed to search for the relationship between the motivation of learning and academic achievement among the students of Ziri bin MenadSecondary School in Bou-saada, and also aimed to search for the levels of motivation and academic achievement among the sample, and also investigated the differences in motivation among the sample according to gender and age, where the sample size of the study was from the students of the second year secondary 210 individuals, and applied the descriptive method of comparison, and reached the following results: - There is a strong statistically significant correlation between the motivation of learning and academic achievement among the students of Ziri bin Menad Secondary School in Bou-saada. - There is a strong statistically significant correlation between participation and academic achievement among students of Ziri bin Menad Secondary School in Bou-saada. - There is a strong statistically significant correlation between the effectiveness and academic achievement among the students of Ziri bin Menad Secondary School in Bou-saada. - There is a strong statistically significant correlation between interest and academic achievement among students of Ziri bin Menad Secondary School in Bou-saada. - There is a strong statistically significant correlation between responsibility and academic achievement among the students of Ziri bin Menad Secondary School in Bou-saada. - The level of motivation for learning among the students of Ziri bin Menad high school is high. - The level of academic achievement among the students of Ziri bin Menad Secondary School in Bou-saada is high. - There are no statistically significant differences in the motivation of learning among the students of Ziri bin Menad High School in Bou-saada, based on the gender variant. - There are no significant differences in the motivation of learning among the students of Ziri Ben Menad High School in Bou-saada, due to the age variable.